“You must come with me, loving me, to death” : The Queer Monster in Sheridan Le Fanu’s Carmilla - Haapanen, Tuuli (My University, 2024)
In this thesis, I study the notion of the queer monster presented in Sheridan Le Fanu’s novella Carmilla (1872). Known as the progenitor of the lesbian vampire trope, Carmilla is one of the cornerstone works of Gothic horror and an early work of published queer fiction. The thesis examines the use of the lesbian vampire as a figure opposing male and heteronormative authority and the way the queerness of Carmilla’s titular character impacts its narrative. There is a key focus on the queer relationship between Carmilla’s main characters and its depiction through the lens of monstrosity. The queer monster is examined as a romantic figure as well as a literary monster functioning as an antagonistic force. In order to conduct analysis of the queer monster, I cite numerous works that examine both Carmilla and the idea of monstrosity. The framework for the construct of monstrosity primarily uses Jeffrey Jerome Cohen’s “Monster Theory: Reading Culture” as its basis.
Keywords: Sheridan Le Fanu, Carmilla, queer theory, lesbian vampire, monster